Analysis of the Electromagnetic Vibration Absorber (EMVA) Mechanism Placement in the MDoF System towards Vibration Reduction and Generated Electrical Energy - Wiwiek Hendrowati; Aida Annisa Amin Daman; Nugraha Merdekawan (JMES The International Journal of Mechanical Engineering and Sciences, 2023)
This research was conducted to determine the effect of the position of Electromagnetic Vibration Absorber (EMVA) to reduce the vibration of main system and to generate the energy. This article reports the results of a simulation and experimental study on the main system, which was excited by external force and the resulting vibration was reduced with an EMVA. The design of EMVA is in laboratory scale. The main system consists of a flat plate as a main mass and four springs, which are subjected to an excitation force that comes from the DC motor. The results show that both the simulation approach and experiment correspond well. The reduction of main system’s vibration is found to be affected by the position of EMVA. The maximum reduction in translation, rolling, and pitching direction occur at different position, which are at point 7 for translation and at point 1 for rolling and pitching. Meanwhile, the highest power generation occurs when the EMVA is at point 1.